Answers

2015-01-15T18:14:00+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
The equation editor is not properly working so i write in the normal text. 

b^2- 4 ac = (p+q)^2 - 4 pq = (p-q)^2

If the roots of the given equation  both are equal, then the discriminant is 0.
   then (p-q)^2 = 0.  Hence  p = q.

if p= q, then  equation will be x^+2x+1=0,  hence roots are equal and = -1.

If  p > q and  q > p  -- in these case real roots exist  but they are not equal.


1 5 1
2015-01-15T19:10:19+05:30
ATQ  
px² + (p+q)x + q = 0
⇒ px² + px + qx  + q = 0
⇒ px(x+1) +q (x +1) = 0
⇒ (px+q)(x+1) = 0
Then we have either px+q= 0 or x+1=0
       px +q =0  ⇒ x = -q/p
 and x + 1 = 0  ⇒ x = -1
This gives - q/p = -1
           ⇒  p = q

1 5 1